Sub-national level of participation in international environmental cooperation: the role of Shiga Prefecture for Lake Biwa environment in Japan - Takao, Yasuo (Routledge, 2013)
From a state-centric view, sub-national level of participation at the international level can be only feasible if it is an active part of national policy. In the case of Shiga prefectural government’s initiative for international lake-environmental cooperation, however, sub-national actors came to see themselves as direct players in the absence of national policy. This study examines under what conditions and in what ways such sub-national level of participation takes place by conducting a case study of Shiga’s collaboration with the United Nations Environmental Programme (UNEP) over lake-environment risk reduction. It reveals the formation process of transnational governance networks involving the sub-national government that is not operating on behalf of the national government. The ultimate objective is to present a case study of working with information in the non-European Union (EU) settings toward building an analytical framework for the participation of sub-national governments in transnational environmental governance. The article finds that the process of Shiga’s participation in transnational governance will have the less chance of being duplicated effectively in other Japanese sub-national governments. Shiga’s cooperation with the UNEP was primarily driven by the ad hoc bottom-up political mobilization of the sub-national actors. In general, without institutionalized channels for sub-national governments to participate in the regional/international level, sub-national governments need to mobilize resources on such an ad hoc basis and only pioneering sub-national actors are capable of effectively engaged on unfamiliar territory with the formation process of transnational governance.